Beispiel Nr: 07
$ \text{Gegeben:}\\\text{Breite} \qquad b \qquad [m] \\ \text{Länge} \qquad a \qquad [m] \\ \\ \text{Gesucht:} \\\text{Umfang} \qquad U \qquad [m] \\ \\ U = 2\cdot a + 2\cdot b\\ \textbf{Gegeben:} \\ b=6m \qquad a=16m \qquad \\ \\ \textbf{Rechnung:} \\ U = 2\cdot a + 2\cdot b \\ b=6m\\ a=16m\\ U = 2\cdot 16m + 2\cdot 6m\\\\U=44m \\ \small \begin{array}{|l|} \hline b=\\ \hline 6 m \\ \hline 60 dm \\ \hline 600 cm \\ \hline 6\cdot 10^{3} mm \\ \hline 6\cdot 10^{6} \mu m \\ \hline 0,006 km \\ \hline \end{array}\\ \small \begin{array}{|l|} \hline a=\\ \hline 16 m \\ \hline 160 dm \\ \hline 1,6\cdot 10^{3} cm \\ \hline 1,6\cdot 10^{4} mm \\ \hline 1,6\cdot 10^{7} \mu m \\ \hline 0,016 km \\ \hline \end{array}\\ \small \begin{array}{|l|} \hline U=\\ \hline 44 m \\ \hline 440 dm \\ \hline 4,4\cdot 10^{3} cm \\ \hline 4,4\cdot 10^{4} mm \\ \hline 4,4\cdot 10^{7} \mu m \\ \hline 0,044 km \\ \hline \end{array}\\$